Deficiencies in Cellular Processes Modulated by the Retinoblastoma Protein Do Not Account for Reduced Human Cytomegalovirus Replication in Its Absence - VanDeusen, Halena R. (J Virol, 2015)
Despite encoding multiple viral proteins that modulate the retinoblastoma (Rb) protein in a manner classically defined as inactivation, human cytomegalovirus (HCMV) requires the presence of the Rb protein to replicate efficiently. In uninfected cells, Rb controls numerous pathways that the virus also commandeers during infection. These include cell cycle progression, senescence, mitochondrial biogenesis, apoptosis, and glutaminolysis. We investigated whether a potential inability of HCMV to regulate these Rb-controlled pathways in the absence of the Rb protein was the reason for reduced viral productive replication in Rb knockdown cells. We found that HCMV was equally able to modulate these pathways in the parental Rb-expressing and Rb-depleted cells. Our results suggest that Rb may be required to enhance a specific viral process during HCMV productive replication. IMPORTANCE The retinoblastoma (Rb) tumor suppressor is well established as a repressor of E2F-dependent transcription. Rb hyperphosphorylation, degradation, and binding by viral oncoproteins are also codified. Recent reports indicate Rb can be monophosphorylated, repress the transcription of antiviral genes in association with adenovirus E1A, modulate cellular responses to polycomb-mediated epigenetic methylations in human papillomavirus type 16 E7 expressing cells, and increase the efficiency of human cytomegalovirus (HCMV) productive replication. Since Rb function also now extends to regulation of mitochondrial function (apoptosis, metabolism), it is clear that our current understanding of this protein is insufficient to explain its roles in virus-infected cells and tumors. Work here reinforces this concept, showing the known roles of Rb are insufficient to explain its positive impact on HCMV replication. Therefore, HCMV, along with other viral systems, provide valuable tools to probe functions of Rb that might be modulated with therapeutics for cancers with viral or nonviral etiologies.